Capturing India’s Sweet Tooth during Pandemic: Analysis of Populace Perception; Practice by Descriptive, Inferential Analysis by SPSS and GIs Choropleth Mapping - Dr. Parimita (International Journal of Modern Agriculture, 2020)
Indians have an immense sweet tooth. Consumption of sugar & sweet has been highly-liked and inherent part of Indian culture, religion and traditions from primeval times. In this study the survey conducted to collect information on demographic data, awareness and attitudes toward sweet consumption before and during lockdown period, this study included 203 subjects. Most of the respondents belong to same socio-demographic profile i.e. college going, non/part time working, unmarried middle class north Indian males from nuclear families. preferred khoa based sweets as their first choice. Top three sweets which were made at home by our respondents were gulab jamun (made by 54.3%), besan laddu (made by 17.3%), and ras malai (made by 14.2%).78.8% respondents gave 5 and above rating. So it can be concluded that this result is in accordance with the fact that sweets are essential and intrinsic part of Indian culture. It is observed that there is a statistically significant reduction in buying sweets During COVID19 period compared to pre COVID19.)